Le Droit À L’eau: Un Droit Fondamental Des Autres Droits De L’homme - Tak, Ziad (European Scientific Journal, ESJ, 2017)
The right to water is a right for all and must be implemented in a nondiscriminatory manner in accordance with the conditions and limits laid down by some particular laws and regulations. In order to make the right to drinking water and sanitation a reality, water and sanitation services must be made affordable to the population as a whole. Property and access to other human rights such as the right to housing, food or health services should also be made available to the population. Internationally, several countries have recognized the right to drinking water and sanitation, but have not actually implemented it at the national level. The objective of this study is to show the importance of the implementation of the right to drinking water, so that it can be made available to all. Since the most widely traded studies on human rights were dominated by political and judicial character, I tried in this study to broaden the meaning of human rights and to provide more Rights. This is despite the fact that it has not been compensated by specific legal texts. As a result, the problem of the study is focused on water as a fundamental need of human, and access to water is part of its fundamental rights.